The personal impacts of having a partner with problematic alcohol or other drug use: descriptions from online counselling sessions. (4th July 2018) - Wilson, Samara R.; Lubman, Dan I.; Rodda, Simone; Manning, Victoria; Yap, Marie B. H.
Abstract: Background: Previous studies have identified that problematic alcohol and other drug (AOD) use has major impacts on family members. Work with partners suggests they experience mental health problems, such as depression, anxiety, or stress, which arise from feelings of helplessness, self-blame, uncertainty, worry, conflict and disruption to family life. However, most studies have focussed on interviews with participants purposively recruited from face-to-face settings. Whether these issues are common to a broader range of partners seeking help and advice from online services requires further study. Method: One hundred synchronous online chat counselling transcripts of partners of individuals with problem AOD use were sampled from a 24-hour national online counselling service in Australia. Thematic analysis was used to look at the personal impacts reported by these partners. Results: The personal impacts identified were reflected in partners' cognitions (depressive cognitions, responsibility beliefs, and thoughts around trust), behaviours (helpful and unhelpful coping) and emotions (anger, sadness, and fear). Conclusions: These findings highlight the substantial burden that problematic AOD use imposes on intimate partners personally, reinforcing the need for services to engage partners as valid help-seekers in their own right.